Keeping It Clean: Controlling Mildew - Mary N. Harrison; Randall A. Cantrell; Amanda Griffin (EDIS)
Mildew is a mold that can grow and cause damage to your health and home. The concern about mildew is that it is believed to contribute to respiratory problems, like asthma, especially in children. This revised 1-page fact sheet provides tips for preventing mildew and for getting rid of it. Written by Mary N. Harrison, Randall A. Cantrell, and Amanda Griffin, and published by the UF Department of Family, Youth and Community Sciences, May 2014.